First record of an unsuccessful parturition of a southern right whale (Eubalaena australis) at Península Valdés, Argentina - Sironi, Mariano Miguel; Marón, Carina Flavia; Petitte, Luis; Guevara, Justa; Martorel, Juan Pablo; Rowntree, Victoria J. (Marine Mammal Science)
Southern right whale (Eubalaena australis) populations were severelydepleted in past centuries by intensive whaling, but many are now recover-ing after receiving international protection in 1935 (IWC 2012). In the SouthAtlantic, the population of southern right whales that migrates each australwinter to calve at Península Valdés, Argentina (Payne 1986; IWC 2001,2012), began experiencing unusually high calf deaths in 2003. The deathspeaked in 2012 with 113 dead calves (Rowntreeet al. 2013, Sironiet al.2018). The estimated age of dead calves ranged from 1 d to 4–6mo(Rowntreeet al. 2013, McAlooseet al. 2016). Fil: Sironi, Mariano Miguel. Universidad Nacional de Córdoba. Facultad de Cs.exactas Físicas y Naturales. Departamento de Diversidad Biológica y Ecológica. Cátedra de Biología del Comportam. y Div. Animal Ii; Argentina. Instituto de Conservacion de Ballenas; Argentina Fil: Marón, Carina Flavia. Universidad Nacional de Córdoba. Facultad de Cs.exactas Físicas y Naturales. Departamento de Diversidad Biológica y Ecológica. Cátedra de Biología del Comportam. y Div. Animal Ii; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Petitte, Luis. Southern Spirit Whale Watch; Argentina Fil: Guevara, Justa. Southern Spirit Whale Watch; Argentina Fil: Martorel, Juan Pablo. Southern Spirit Whale Watch; Argentina Fil: Rowntree, Victoria J. University Of Utah. Department Of Biology; Estados Unidos